Effect Of Relaxation Education Acupressure For Increasing Knowledge Nurse At H. Andi Sulthan Daeng Radja Bulukumba Hospital - Nadia Alfira; A.Nurlaela Amin; Novitasari; Darmila (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Background : _ Knowledge is results from know somebody to object through the senses he has ie senses hearing , senses smell , senses sight , senses smell , and senses touch . Knowledge is something known _ related with the learning process . Learning process This influenced a number of factor from in , like motivation and factors outside form means available information , as well circumstances social culture . Research purposes : He knows influence giving education relaxation acupressure to enhancement knowledge nurse at H. Andi Sulthan Daeng Radja Bulukumba Regional Hospital. Research method : Research design used _ in study This is design pre-experimental with big the sample is 39 people with use technique taking sample that is consecutive sampling . Results: Research results This using statistical tests Wilcoxon test _ show that before given education technique relaxation acupressure obtained category Enough as much as 17.9% and less as much as 82.1%. whereas after given education technique relaxation acupressure obtained category Good as much as 94.9% and sufficient as much as 5.1%. Based on pre-test and post -test results show exists difference knowledge nurse before and after given education relaxation acupressure . Conclusions and suggestions: On research This can be concluded that knowledge nurse before given education technique relaxation acupressure obtained that nurse more Lots own knowledge lack , knowledge nurse after given education technique relaxation acupressure obtained that nurse more Lots own knowledge OK , and there is difference knowledge nurse before and after given education relaxation acupressure . As for suggestions in study This for nurses to further increase their knowledge of acupressure relaxation techniques with existing education or learning, so that nurses in this case can share their knowledge with patients, families and other nurses.